Synergistic heterojunction effects in Ag3PO4/SnO2 nanocomposites: a photocatalytic study on isoproturon degradation - Ram, Rishi; Bhawna,; Kumar, Sanjeev; Gupta, Akanksha; Kumar, Ravinder; Dubey, Kashyap Kumar; Kumar, Vinod (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPesticides such as isoproturon are widely employed and represent a considerable environmental concern. The development of sustainable and efficient degrading techniques is crucial. Photocatalytic degradation employing semiconductor materials is a compelling solution. This study examines the synergistic advantages of heterojunction formation by synthesizing, characterizing, and improving the photocatalytic efficacy of Ag3PO4/SnO2 nanocomposites for the degradation of isoproturon.MethodsThe Ag3PO4/SnO2 nanocomposite was characterised using powder X-ray diffraction (PXRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Ultraviolet-Diffuse Reflectance Spectroscopy (UV-DRS) and X-ray Photoelectron Spectroscopy (XPS). The effective synthesis of the Ag3PO4/SnO2 heterojunction was confirmed by characterization data from various techniques (PXRD, FTIR, SEM, UV-DRS, XPS).Results and DiscussionElemental mapping confirmed uniform distribution of O, P, Ag, and Sn. High-resolution mass spectrometry (HRMS) was employed to analyse degradation products. The Ag3PO4/SnO2 nanocomposite exhibited improved photocatalytic degradation of isoproturon compared to its precursors. In contrast to 25% for pure SnO2 and 41% for Ag3PO4, over 97% degradation was achieved using Ag3PO4/SnO2 nanocomposite within 120 min of light irradiation under identical conditions. The synergistic effects of heterojunction formation significantly enhanced isoproturon degradation using the Ag3PO4/SnO2 nanocomposite. The heterojunction reduces electron-hole recombination rate and enhances photogenerated charge carriers for degradation via effective charge separation. The improved photocatalytic activity is ascribed to the increased surface area of the nanocomposite. The analysis of HRMS data revealed the degradation products. The findings demonstrate the efficacy of Ag3PO4/SnO2 nanocomposites as photocatalysts for environmental remediation, namely in the breakdown of pesticides.